Pengaruh ekspor impor terhadap pertumbuhan ekonomi pada tahun 2009 – 2019 di Indonesia - S. Nurdani, Alya; M. Puspitasari, Devy (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine how exports and imports affect economic growth in Indonesia. The type of data used in this study is statistical data from BPS (Central Bureau of Statistics) 2009 - 2019 in Indonesia which is descriptive verification and quantitative in nature and is used to obtain empirical evidence of the influence of independent variables to process data using multiple linear regression analysis in which several assumption tests are processed using Eviews 10 software. The results of the study found that exports have a positive and significant effect on economic growth in Indonesia. While imports have a negative and significant effect on economic growth in Indonesia.